ANALISIS KEPUASAN MASYARAKAT PADA KANTOR PELAYANAN PERIZINAN TERPADU (KPPT) KOTA MOJOKERTO - sukesi, Sukesi (Ekspektra : Jurnal Bisnis dan Manajemen, 2017)
The significance of quality is valuable to the satisfaction of society is the company's capital in selling service products. Without exception public companies are improving both service quality and products. Service quality should be done consistently, KPPT Mojokerto City as the providers of public service, whose populated with UMKM business areas. It’s required to provide quality services not only value, but the convenience of service. In order to know (1)The level of community satisfaction the service of KPPT Mojokerto City;(2)And Analyze the results of the assessment of SKM. Qualitative descriptive and 9 elementsanalysis tools and 18 indicators of assessment are developing, based on Peraturan Menteri PAN-RB No.16 2014 about SKM guidelines for Public Service Providers. Research using random sampling accidental proportional gain 100 respondents. The result of all variables, the level of user service satisfaction, has score category B (good). The result of index score 76.35 means that, generally satisfaction society in a good category. With index of service quality as the expectations from willingness to give positive response for each type of product service. For advice, it’s should be able to provide transparency of services related to applicant for permits regarding provisions/rules/standards costs on each type of license. Keywords:Qualitative,Research,service quality, public service,satisfaction society